Menstrual Regulation as a Means of Reproductive Control: The Law's Response to Disabled Bodies and Menstruation - Ni Fhlatharta, Maria (Columbia Journal of Gender and Law, 2021)
Every day, millions of people make decisions about menstruation. They make decisions about what sanitary products to use, about pain relief, about with whom they will discuss their experience of menstruation. They make decisions about contraception to induce amenorrhea. These decisions may be influenced by family, poverty, society, and culture, but they remain, for the most part, up to the individual. However, this right to autonomy is not extended to all people equally. Some disabled people, for example, have these decisions made by substituted decision makers, including the courts. This is in violation of their rights; nevertheless, this practice continues in various jurisdictions, including through guardianship and conservatorship laws.